2018
DOI: 10.1590/s2175-97902018000417773
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of resveratrol as an adjuvant with meloxican in the treatment of knee osteoarthritis patients: A double-blind, randomised, placebo-controlled trial

Abstract: The present study aimed to evaluate the effect of the adjuvant use of resveratrol with meloxicam on the clinical scores of knee OA patients. This was a double-blind placebo-controlled randomised trial involving 100 patients with knee osteoarthritis performed at the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Two recent clinical studies confirmed the involvement of resveratrol in managing knee OA pain and its associated symptoms [ 51 , 67 ]. Supplementation of 500 mg/day resveratrol led to increased aggrecan serum levels and significantly improved pain, although no significant decrease in serum levels of IL-6, IL-1β, and TNF- α was observed [ 56 ].…”
Section: Efficacy and Mechanism Of Action Of Polyphenolsmentioning
confidence: 94%
See 1 more Smart Citation
“…Two recent clinical studies confirmed the involvement of resveratrol in managing knee OA pain and its associated symptoms [ 51 , 67 ]. Supplementation of 500 mg/day resveratrol led to increased aggrecan serum levels and significantly improved pain, although no significant decrease in serum levels of IL-6, IL-1β, and TNF- α was observed [ 56 ].…”
Section: Efficacy and Mechanism Of Action Of Polyphenolsmentioning
confidence: 94%
“…This nutraceutical has many health-benefiting properties, including its anti-inflammatory, antioxidant, and anticancer properties. By modulating major oxidative stress signaling pathways, resveratrol has become one of the most studied nutraceuticals in managing degenerative diseases such as OA [ 51 , 52 , 54 , 55 , 56 , 57 , 67 ] ( Table 1 ).…”
Section: Efficacy and Mechanism Of Action Of Polyphenolsmentioning
confidence: 99%
“…Additionally, KOOS subscales for functional and activity status were also dramatically improved. The significant clinical improvement in the symptoms and stiffness was predicted because antinociceptive and anti-inflammatory effects of resveratrol can be obtained even within short-term treatment as reported by our previous reports and pilot interventional study on the efficacy of coadministration of resveratrol with meloxicam in patients with knee osteoarthritis [ 29 , 30 ]. Additionally, other studies demonstrated weak or no significant correlations between aggrecan levels and any of the relevant clinical presentations of OA such as morning stiffness, knee pain, local knee warmth, and other symptoms expressed by Lequesne functional index and Western Ontario and McMaster Universities Arthritis Index (WOMAC) score.…”
Section: Discussionmentioning
confidence: 89%
“…It was pointed out that the dosage used or the therapy duration should be reconsidered and the severity of the impairment might not be able to be improved by resveratrol. In the treatment of knee osteoarthritis, intervention of resveratrol as an adjuvant of meloxicam, daily intake of resveratrol (500 mg) combined with meloxicam could significantly improve pain and symptom scores in the mild-to-moderate knee osteoarthritis patient after a 90-day treatment . Surprisingly, as demonstrated by the same group of the research team, intervention of resveratrol had led to a secondary outcome, including reducing serum cholesterol, triglyceride, urea, and creatinine .…”
Section: Clinical Studies With Supplementation Of Stilbenoidsmentioning
confidence: 97%
“…In the treatment of knee osteoarthritis, intervention of resveratrol as an adjuvant of meloxicam, daily intake of resveratrol (500 mg) combined with meloxicam could significantly improve pain and symptom scores in the mild-to-moderate knee osteoarthritis patient after a 90day treatment. 141 Surprisingly, as demonstrated by the same group of the research team, intervention of resveratrol had led to a secondary outcome, including reducing serum cholesterol, triglyceride, urea, and creatinine. 142 In some cases, resveratrol showed no effect on the outcome expected, but it could be due to several possible reasons to be considered in future studies.…”
Section: Clinical Studies With Supplementation Of Stilbenoidsmentioning
confidence: 98%